The lacteus-, laspeyresiella- and mycetophilus-groups of Apanteles Foerster, 1862 (Hymenoptera, Braconidae, Microgastrinae) in China, with descriptions of eight new species - Liu, Zhen; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2015)
The lacteus-, mycetophilus- and laspeyresiella-groups of the genus Apanteles Foerster (Hymenoptera, Braconidae, Microgastrinae) are newly recorded from China with eight new species being described, namely A. basicavus Liu & Chen, sp. n. of the lacteus-group; A. brevivena Liu & Chen, sp. n. and A. parapholetesor Liu & Chen, sp. n. of the mycetophilus-group; A. artustigma Liu & Chen, sp. n., A. hainanensis Liu & Chen, sp. n., A. magnioculus Liu & Chen, sp. n, A. sparsus Liu & Chen, sp. n. and A. thoracartus Liu & Chen, sp. n. of mycetophilus-group. Two newly recorded species of the mycetophilus-group are described and illustrated. Keys to the Chinese species of those groups are provided.